Implementation of Islamic Law in an Integrated Service System Organized Electronically by the National Land Office - Maysarah, Maysarah; Ananda, Faisar; Fuad, Phil Zainul (SASI, 2024)
Introduction: One of the important academic issues is in the form of a judge's decision in Case Number 811/Pdt.G/2020/PN.Medan, in the form of ratification of inherited objects. Its implementation is contrary to Article 24 paragraph (2) of the 1945 Constitution, The highest judicial power is exercised by the Supreme Court in UU no. 5 of 2004 concerning Amendments to Law Number 14 of 1985 concerning the Supreme Court, Law Number 5 of 2004, due to Pergub) Number 117 of 2019 as executor of Minister of Finance Regulation Number 32/PMK.03/2005 regulates profit sharing central and regional governments, Number 186/PMK/07/2010 and Number 53 of 2010 concerning the application of tax rates for the acquisition of land and building rights (BPHTB), as well as stipulating Regional Regulation (Pergub) Number 60 of 2021, not all of which can be processed as objects inheritance.Purposes of the Research:  To analyze the Legal Basis for the Electronic/Online Integrated Service System Organized by the National Land Agency of North Jakarta Administrative City based on the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of National Land Agency RI Number 5 of 2017 concerning Electronic/Online Land Information Services , regarding the implementation of the Regulation of the Minister (Permen) of Agrarian and Spatial Planning of the Head of the National Land Agency of the Republic of Indonesia Number 16 of 2017 as the legal basis for the electronic/online Integrated Service System organized by the North Jakarta Administrative City Land Agency.Methods of the Research: This research method is normative-empirical with a case approach, statutory approach and comparative approach. The theories used are the theory of legal certainty, the theory of justice and the maqashid syari'ah theory. Primary data used are interviews, documentation and observation, secondary data is the Koran Hadith, laws, books and journals.Results of the Research: The results of the research are based on a. The legal basis for the Integrated Electronic/Online Service System Organized by the North Jakarta Administrative City National Land Agency (BPN), b. Implementation of the Integrated Service System (SiPandu) at the North Jakarta Administrative City National Land Agency (BPN), c. Problems with the Implementation of the Integrated Service System (SiPandu) in the North Jakarta Administrative City National Land Agency (BPN), Views of the North Jakarta Administrative City Council of Indonesian Ulemas (MUI) on the Integrated Service System (SiPandu) in the North Jakarta Administrative City National Land Agency (BPN), very contrary to the rules governing Presidential Regulation Number 95 of 2018 concerning Electronic-Based Government Systems (SPBE), Ministerial Regulation (Permen) of Agrarian Affairs and Spatial Planning (ATR) of the Head of the National Land Agency of the Republic of Indonesia (KBPN) Number 16 of 20212 is an amendment to Regulation of the Minister (Permen) of the State for Agrarian Affairs/Head of Agency Government Regulation Number 3 of 1997 concerning Implementing Provisions of Government Regulation Number 24 of 1997 concerning Land Registration2 implemented by Number 5 of 2017 and Law Number 25 of 2009 concerning Public Services, development planning and the settlement of land conflict problems in the regions at the end of 2025 has E-Certificates throughout Indonesia, not the implementation through SiPandu electronically/online is held by the Land Agency of North Jakarta Administrative City